Baitulmal and its role in economic development / Nurul Afaf Binti Zainon - Zainon, Nurul Afaf (Academy of Contemporary Islamic Studies (ACIS), 2017)
Treasury is one of the mechanisms established officially by Saidina Umar Al-Khattab to manage state property for the economic interests of the Muslims. However, in the treasury function has been adjusted in accordance with the constitution and managed by the State Islamic Council. Thus, this study intends to identify the management of Baitulmal in Malaysia by focusing the Selangor Islamic Religious Council (MAIS) as treasury. The study was conducted in Selangor. Conclusion of the study found that MAIS have done many efforts in order to promote Baitulmal products to society and the management of Baitulmal mostly focusing in trust property. MAIS as treasury roles in managing the trust property and it was supported by the trend of revenue collection and treasury MAIS property.